Jobs. - Freeland, Sherry (Education Digest, 1984)
The article focuses on the occupations that are likely to have the most job openings through the mid-1990's in the U.S. The federal government's biennial Occupational Outlook Handbook projects a very rapid proportional growth for computer-related occupations, with service technician jobs expected to increase by 97 percent. Health occupations constitute another growing field, the federal government says. However, it points out that successful efforts to contain health-care costs will come at the expense of health-care workers. Medical school graduates will have a hard time finding residency positions, the Labor Department predicts, because there are so many medical students. The job outlook for elementary school teachers is expected to improve in response to increased birth-rates in the late 1970's and early 1980's. Construction and production jobs will also be on the rise.